PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATAN HASIL BELAJAR FISIKA PADA SISWA KELAS XI MIPA 1 SMA NEGERI 1 PETANG - I WAYAN SUINDHIA (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2022)
This researcher aims to find out the application of the demonstration method to improve student defense results in physics subjects for class XI MIPA 1 Semester 1 students at SMA Negeri Petang in the 2022 /2023 academic year. The research design used in this study was classroom action research (PTK). Based on the results of research that has been carried out, it is concluded that the application of demonstration methods can increase the hasil belajar students of Class XI MIPA 1 Semester 1 SMA Negeri 1 Evening in physics subjects in the academic year 2022/2023. The learning outcomes of class XI MIPA 1 students in the subject matter of Static Fluid Physics have an improvement in each cycle. In the pre-cycle stage of 32 students of class XI MIPA 1, who have learning outcomes reaching KKM 75 scores as many as 16 students or 51,61% while the remaining 15 or 48,39% of students do not reach KKM 75 or do not pass with the average grade point average score of 55,50. Furthermore, in the first cycle, student learning outcomes showed an increase, namely, from 32 students of class XI MIPA 1 as many as 24 students or 77,41% passed or reached KKM 75, while as many as 7 students or 22,59% have not reached KKM 75 or did not graduate with an average grade point average score of 73.25. In cycle II as the last cycle showed a better improvement with the results of 32 students of class XI MIPA 1 there were 28 or 90,32% of students who graduated or reached KKM 75 while there were only 3 students or 9,68% of students who had not graduated or did not reach KKM with an average score class of 82.25. ABSTRAKPenelitian ini bertujuan untuk mengetahui penerapan metode demonstrasi untuk meningkatkan hasil belajar siswa dalam mata pelajaran Fisika siswa kelas XI MIPA 1 Semester 1 di SMA Negeri Petang tahun pelajaran 2022/2023. Rancangan penelitian yang digunakan dalam penelitian ini adalah penelitian tindakan kelas (PTK). Berdasarkan hasil penelitian yang telah dilakukan dapat disimpulkan bahwa penerapan metode demonstrasi dapat meningkatkan hasil belajar siswa Kelas XI MIPA 1 Semester 1 SMA Negeri 1 Petang pada mata pelajaran Fisika tahun pelajaran 2022/2023. Adapun hasil belajar siswa kelas XI MIPA 1 pada mata pelajaran Fisika materi pokok Fluida Statis memiliki peningkatan dalam setiap siklusnya. Pada tahap pra siklus dari 32 siswa kelas XI MIPA 1, yang memiliki hasil belajar mencapai nilai KKM 75 sebanyak 16 siswa atau 51,61% sedangkan sisanya sebanyak 15 atau 48,39% orang siswa tidak mencapai KKM 75 atau tidak lulus dengan nilai rata-rata kelas sebesar 55.50. Selanjutnya pada siklus I hasil belajar siswa menunjukan peningkatan yaitu, dari 32 siswa kelas XI MIPA 1 sebanyak 24 siswa atau 77,41% lulus atau mencapai KKM 75, sedangkan sebanyak 7 siswa atau 22,59% belum mencapai KKM 75 atau tidak lulus dengan nilai rata-rata kelas sebesar 73.25. Pada siklus II sebagai siklus terakhir menunjukan peningkatan yang lebih baik dengan hasil dai 32 siswa kelas XI MIPA 1 terdapat 28 atau 90,32% orang siswa lulus atau mencapai KKM 75 sedangkan hanya ada 3 siswa atau 9,68% orang siswa yang belum lulus atau tidak mencapai KKM dengan nilai rata-rata kelas sebesar 82.25.